(x-2)+1+3x=5(x+1)

Simple and best practice solution for (x-2)+1+3x=5(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)+1+3x=5(x+1) equation:


Simplifying
(x + -2) + 1 + 3x = 5(x + 1)

Reorder the terms:
(-2 + x) + 1 + 3x = 5(x + 1)

Remove parenthesis around (-2 + x)
-2 + x + 1 + 3x = 5(x + 1)

Reorder the terms:
-2 + 1 + x + 3x = 5(x + 1)

Combine like terms: -2 + 1 = -1
-1 + x + 3x = 5(x + 1)

Combine like terms: x + 3x = 4x
-1 + 4x = 5(x + 1)

Reorder the terms:
-1 + 4x = 5(1 + x)
-1 + 4x = (1 * 5 + x * 5)
-1 + 4x = (5 + 5x)

Solving
-1 + 4x = 5 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-1 + 4x + -5x = 5 + 5x + -5x

Combine like terms: 4x + -5x = -1x
-1 + -1x = 5 + 5x + -5x

Combine like terms: 5x + -5x = 0
-1 + -1x = 5 + 0
-1 + -1x = 5

Add '1' to each side of the equation.
-1 + 1 + -1x = 5 + 1

Combine like terms: -1 + 1 = 0
0 + -1x = 5 + 1
-1x = 5 + 1

Combine like terms: 5 + 1 = 6
-1x = 6

Divide each side by '-1'.
x = -6

Simplifying
x = -6

See similar equations:

| 16x^2+24x+9=6 | | 12x+12=5x+96 | | 79-5x=13x+21 | | 5(x+1)-6x=3x-9 | | c-5c+7c= | | cos(x)+2x=0 | | 4x-1×(0.5)3-2x=1/8-x | | x*x+2x-23.333=0 | | 12+9x=6x | | 0.65=0.3+0.7x | | 5(x/6-x/2)-7(x/2-x/4)=9 | | 5(x/6-x/2)-80 | | x:2x+9=6 | | 30(a*a*a)*2(a*a*a*a)=1 | | (5x+3y)=360 | | 3xsquare+x-5=0 | | 4x-20=3x+8 | | 67x-4*9=0 | | (6-2x)/(6x-x^2)=0 | | mx+m=x^2+2mx+1 | | x^2+mx+1-m=0 | | -16x^3+x^2+16=0 | | z^11/7z^2 | | 3g+5d= | | 3g+5d=1 | | y=3x+4findy | | 40-x=32 | | ln(-x^2+6x)=0 | | 24=7y+3 | | x+1,5=5,5 | | 5y-2=52 | | (4/5)-0.08x=0 |

Equations solver categories